Amino‐functionalization of carbon fibers through electron‐beam irradiation technique. Issue 10 (19th December 2013) - Mao, Lian; Wang, Yuansheng; Zang, Zhenjuan; Zhu, Shanshan; Zhang, Haisheng; Zhou, Huihui
Abstract Amino‐functinonalized carbon fibers were achieved via electron‐beam (EB) irradiation in Diethylenetriamine (DETA) solution and triethylene tetramine (TETA) solution at 200 kGy. Different graft monomer concentrations were investigated to find the optimal concentration of each graft monomer. X‐ray photoelectron spectroscopy, scanning electron microscopy, and Raman spectroscopy were applied to investigate chemical composition and functional groups, topography and disorder degree of amino‐functionalized carbon fibers surface. Meanwhile, adsorption ability and interfacial adhesion between modified carbon fibers and epoxy resin were determined by TGA and interlaminar shear strength (ILSS). It is found that amino‐functionalized carbon fibers which had rougher and more active surface performed better adsorption ability on epoxy resin than untreated fibers. The optimal ILSS values of carbon fiber (treated with DETA and TETA) reinforced composites were 21.37 MPa and 18.28 MPa, which were much higher than that of untreated fiber reinforced composites. The comprehensive results demonstrated that in this condition, the optimal grafting concentrations of both DETA and TETA were 1.5 mol/L. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40274.